LEGAL PROTECTION OF VICTIMS OF CHILDREN VIOLENCE - Dara Savira; Munawir Pasaribu (Proceeding International Seminar of Islamic Studies, 2021)
Violence against children is an act of physical, sexual, abuse or emotional violence against children. Actions of violence against children often occur, including in the area of Bandar Khalipah Village, Dusun XVI, parents in this area often vent their frustration on children which is the cause of the problem of violence against children namely family factors, economic factors, or financial factors because in fact between your spouse and your children are your enemies so be careful of them. The purpose of this research is to prevent or protect children from acts of violenceThe subjects of this study were some children who had been subjected to violent acts both physically and mentally.The method used is a qualitative method in the form of a case study.Keywords: legal protection' children violence' children victim'